ANALISIS KUALITAS PELAYANAN PENYULUHAN HUKUM DALAM MENINGKATKAN KESADARAN HUKUM - Firnas Adani; Cahyoko Edi Tando (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The high rate of criminality among students and the community in the Magelang area encourages the need for a preventive approach in building legal awareness. The Bambang Solah Program (Balai Pemasyarakatan Sambang Desa lan Sekolah) implemented by the Class II Correctional Center of Magelang is a public service innovation aimed at fostering legal awareness through outreach in schools and the community. This study aims to assess the service quality of the Bambang Solah program as well as to identify supporting and inhibiting factors in its implementation. The study uses a qualitative method with semi-structured interview techniques, observation, and documentation, and is analyzed using the SERVQUAL approach. The results of the study show that the Bambang Solah service is considered good in the aspects of reliability (repetitive and contextual material delivery), responsiveness (method adaptation to participant characteristics), assurance (competence and credibility of the facilitators), and empathy (emotional closeness with participants). However, there are still obstacles such as limited operational budget. Supporting factors include a communicative approach and structural support from the Correctional Center. The conclusion of this study affirms that Bambang Solah is a strategic program in building participatory and educational legal awareness.